Investigating Below the County Level to Reveal Poverty-Related Disparity in Poor Birth Outcomes [A204]. (May 2022) - Hall, Jaclyn; Smith, Erica; Wen, Tony; Reeder, Callie; Layton, Claire; Lemas, Dominick
Abstract : INTRODUCTION: Birth outcome disparity associated with communities of rurality and socioeconomic vulnerability within the state of Florida was examined. Specific challenges suffered by poor communities may be overlooked when reporting standards for health outcomes are at the county level. We hypothesized that birth outcome disparities are more related to neighborhood socioeconomic vulnerability than rurality. METHODS: Data for Florida births from 2013 to 2017 were obtained from FLHealthcharts.com . Maternal counties of residence were identified as rural or non-rural by the population density measure used by the Florida Department of Health. The Centers for Disease Control and Prevention's index for socioeconomic status vulnerability (SEV) was incorporated for residential census tracts, which were divided into higher and lower vulnerability halves. The prevalence of preterm (PTB) and low-weight birth (LBW) was calculated for each outcome. Statistical significance of birth outcome disparity was tested using rate ratio statistical test. RESULTS: Residing in a rural area was associated with a significant disparity of 7% higher rate for PTB and 2% higher rate for LBW. Residing in a community with high SEV was associated with a larger disparity. High SEV is associated with 18% higher PTB and 28% higher LBW risk than residing in low SEV. CONCLUSION: The health burden related to socioeconomic vulnerability is higher than the disparity related to rurality. Public health studies involving social determinants of health, like birth outcomes, require statistical investigations below the county level. By moving beyond the county as the standard for public health reporting and reporting at the community level, we uncover the burden of health concerns as related to SEV.